Development of Character Makeup Learning Videos for the Makeup and Beauty Department Students - Putri, Adinda Dwi; Rahmiati, Rahmiati (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
Character Make-up is one of the materials consists of theory and practice. Based on the results of observations, it shows that Students have difficulty in determining the theme of character makeup which is the final project in this material. Based on these problems, this study aims to develop learning video on character makeup material. This video can be used as a reference for students looking for character makeup themes to complete assignments in character makeup courses. The method in this research is R&D method, with the Ploomp development model. The stages of the Ploomp model are initial investigation, development and manufacture of prototypes and the assessment phase. The conclusion of the research shows that the resulting character makeup learning video is valid which is shown in the results of the media expert validation test is 0.85 and the material expert validation is 0.88, while the practicality of the lecturers is 82% with practical criteria and the practicality of the students is 93.9% with very practical criteria. The resulting learning video is also effectively used, which is indicated by the difference in the value of student learning outcomes when the posttest is higher than the value of the pretest learning outcomes.